A Review of Oral Therapies for the Treatment of Skin Hyperpigmentation. Issue 2 (March 2022) - Shimshak, Serena J. E.; Tolaymat, Leila M.; Haga, Claire B.; Dawson, Nancy L.; Gillis, Mindy S.; Yin, Mingyuan; Kirsch, Brandon; Cooper, Maria; Sluzevich, Jason C.
This review article examines evidence supporting the use of oral therapies in treating idiopathic, actinic, and metabolically induced skin hyperpigmentation. A thorough review of the literature regarding oral treatments for hyperpigmentation was systematically conducted through PubMed. Keywords used in the primary search include "Hyperpigmentation, " "Melanosis" or "Melasma, " "Lightening, " "Oral, " and "Therapeutics." The search was limited to the English language, and no timeframe restrictions were implemented. Numerous orally administered therapies have been proposed for the treatment of skin hyperpigmentation. There is an abundant body of literature demonstrating the efficacy of orally administered tranexamic acid, glutathione, isotretinoin, and proanthocyanidin. It is reasonable to expect that the most effective oral therapies will address known underlying causes of hyperpigmentation such as thyroid disease, diabetes, and hormonal imbalance. Improvement due to oral therapy of otherwise unresponsive skin hyperpigmentation or hyperpigmentation of unknown cause is less predictable. This review is limited by the strength of evidence contained within the available studies. Clinical studies investigating the treatments discussed within this article are limited in number, at times lack blinding in the study design, and are based on small sample sizes. Based on existing research, the most promising oral remedies for hyperpigmentation appear to be tranexamic acid, glutathione, isotretinoin, and proanthocyanidin. Additional studies to better establish safety and efficacy are necessary.